The T2FLAIR mismatch novel radiogenomic marker in the newly suspected low-grade gliomas - Iulia Miculescu; Daniela L. Ivan; Aurelia Dabu; Daniel Teleanu; A. V. Ciurea (Romanian Neurosurgery, 2023)
Background. The T2-FLAIR (fluid-attenuated inversion recovery) mismatch sign has been defined over the last few years as an important novel radiogenomic marker highly suggestive of isocitrate dehydrogenase mutated (IDH-mut) 1p19q non-codeleted gliomas (astrocytomas). Existing studies have demonstrated that this has good specificity but limited sensitivity for IDH-mut astrocytomas. The new 2021 WHO Classification of Tumors of the Central Nervous System (WHO CNS5) has introduced a layered grading system in which all IDH mutant diffuse astrocytic tumours are considered a single type (Astrocytoma, IDH-mutant) and are graded as CNS WHO grade 2, 3, or 4. Because of the growing importance of molecular information in CNS tumour classification, diagnoses and diagnostic reports need to combine different data types into a single diagnosis. Whether the T2FLAIR mismatch sign is of clinical relevance for the management of low-grade gliomas still needs to be further determined. Methods. We included histologically verified supratentorial low-grade gliomas (LGG) WHO grade 2-3 retrospectively during the period 2013–2018 (n=18). For the period 2019–2023 (n=27), patients with a radiological presumptive diagnosis of low-grade glioma were prospectively included, and we took into consideration the fact that in this group we could encounter other diagnoses than glioma. Clinical, radiological and histology data were collected. We aimed to examine the association of the T2-FLAIR mismatch sign (where identified) with clinical factors and outcomes. We evaluated the diagnostic reliability of the mismatch sign and its relation to the definitive histological diagnosis, the co-existence of an MR spectroscopy signature; we have also tried to determine whether the identification of the radiogenomic marker had any impact on the clinical outcome through the decision-making in neurosurgical management. Results. Out of 45 patients with radiological suspected glioma, 30 had a definitive diagnosis of diffuse astrocytoma grade 2 and 3 (Astrocytoma, IDH-mutant according to WHOCNS5). 6 patients had a diagnosis of glioblastoma (Glioblastoma, IDH-wildtype according to WHOCNS5). 8 patients have been diagnosed with oligodendroglioma (Oligodendroglioma, IDH-mutant, and 1p/19q-codeleted according to WHOCNS5) and 1 case had a definitive histology of cerebral abscess. Out of the 30 patients with IDH-mut astrocytoma, 6 (20.0%) showed a mismatch sign. The sensitivity and specificity of the mismatch sign for IDH-mut astrocytoma detection were 20% and 98.6%, respectively. There were no differences between patients with an IDH-mut astrocytoma with or without T2FLAIR mismatch sign when grouped according to this with related to baseline characteristics, clinical outcome and presenting symptoms. MR spectroscopy sequences were analyzed where available for the retrospective and prospective cohort. There were 7 cases where MR spectroscopy was performed and, for the IDH-mut astrocytoma cases (n=4) it showed a persistent high Cho/NAA ratio without any difference between the patients with or without the T2FLAIR mismatch sign. Conclusion. In our relatively small retrospective and prospective cohorts, the T2-FLAIR mismatch sign, where identified, was not correlated with clinical features at presentation, prognosis or outcome. Until recently, the grading of CNS tumours has been focusing mainly on histology characteristics, but specific molecular markers can now be used for valuable prognostic information. For this reason, molecular-specific information has been added as an essential feature in grading and it is considered very useful for further estimation of prognosis within variable tumor types. We could not determine if the IDH-mut astrocytomas with mismatch sign represent a specific subgroup. Our study has confirmed that the T2-FLAIR mismatch sign is a reliable and specific marker of IDH-mut astrocytomas.